Epidemiology and Outcome in Neonatal and Pediatric Herpes Simplex Encephalitis: A 13-Year Experience in a Singapore Tertiary Children's Hospital - Jeyanthi, Joseph Carolin; Ong, Ian; Guan, Yeo Joo; Subramania, Krishnamoorthy S; Cheng, Thoon Koh (Journal of Pediatric Infectious Diseases, 2015)
Herpes simplex encephalitis (HSE) remains one of the most devastating infections of the central nervous system in children despite available antiviral therapy. Our aim was to determine the clinical epidemiology and long-term neuro-developmental outcome of neonates and children admitted to our hospital with proven HSE. Patients with HSE during November 1998 to December 2011 were identified from discharge and laboratory records and data collection was done by retrospective review of their case notes. HSE was proven by culture or polymerase chain reaction (PCR) or by a positive Herpes simplex virus (HSV)–specific intrathecal antibody. We identified 13 patients during the study period: nine neonates and four older children, all of whom were treated with intravenous acyclovir. In the neonatal cohort, three (33%) presented with seizures and only four (44%) had vesicles. The initial cerebrospinal fluid (CSF) HSV PCR was positive in seven (78%) and HSV type 2 was the most common. Repeat CSF study showed HSV positivity of 100%. Two (22%) neonates died and three (43%) had long-term neurodevelopmental sequelae. Developmental delay, focal neurological deficit, and cognitive deficit were among the most frequent neurological sequelae noted. In the pediatric cohort, three children (75%) had positive CSF HSV PCR and seizures. One (25%) died and two of the three survivors (67%) had neurodevelopmental sequelae. Early CSF studies may be negative in HSE, so a repeat CSF analysis should be considered, particularly in neonates. Early administration of acyclovir could prevent adverse outcomes in HSE.
Keywords: child; encephalitis; herpes simplex; newborn